2020
DOI: 10.3390/admsci10040088
|View full text |Cite
|
Sign up to set email alerts
|

The Artist as Innovation Muse: Findings from a Residence Program in the Fuzzy Front End

Abstract: In a highly competitive business environment, integrating artists into corporate research and development (R&D) seems to be a promising way to foster inventiveness and idea generation. Given the importance of individual level innovation for product development, this study explores the benefits that employees experience from the artist-in-residence-program at Robert Bosch GmbH, Germany. Qualitative content analysis of interviews with scientists and engineers was performed in order to explore the impact of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 90 publications
(116 reference statements)
0
5
0
Order By: Relevance
“…Based upon the academic literature on channel members’ extra-role behaviors (Mandi et al, 2022; Zhou et al, 2020), distributors are usually willing to help focal manufacturers with new technology information, market knowledge and consumer behaviors in a voluntary way. Moreover, as distributors are the only vertical stakeholders that are closely associated with both focal manufacturers and terminal retail markets in practice (Figure 1), they can offer downstream strategic orientation about marketing strategies and information about advanced technologies to focal manufacturers’ upstream FFE strategies to make the NPD process more feasible according to the mutual understanding of firm governance, credibility, dedication and channel dependence from their extra-role behaviors (Kim et al, 2011; Ling-Yee, 2010; Sandberg, 2020). Thus, we believe distributors’ extra-role behaviors of strategic orientating capabilities will help focal manufacturing firms with FFE innovation in the NPD process in this study.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Based upon the academic literature on channel members’ extra-role behaviors (Mandi et al, 2022; Zhou et al, 2020), distributors are usually willing to help focal manufacturers with new technology information, market knowledge and consumer behaviors in a voluntary way. Moreover, as distributors are the only vertical stakeholders that are closely associated with both focal manufacturers and terminal retail markets in practice (Figure 1), they can offer downstream strategic orientation about marketing strategies and information about advanced technologies to focal manufacturers’ upstream FFE strategies to make the NPD process more feasible according to the mutual understanding of firm governance, credibility, dedication and channel dependence from their extra-role behaviors (Kim et al, 2011; Ling-Yee, 2010; Sandberg, 2020). Thus, we believe distributors’ extra-role behaviors of strategic orientating capabilities will help focal manufacturing firms with FFE innovation in the NPD process in this study.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…Zhang and Doll (2001) and Zhang et al (2019) suggested that strategic orientation is one of the FFE mechanisms along with other internal and external FFE activities to establish NPD project targets and priorities that reduce uncertainties by using competitive intelligence. Strategic orientation formulates the holistic premises of direction, decisions and beliefs about FFE strategies (Adams et al, 2019; Hakala, 2011; Sandberg, 2020; Zhang et al, 2019). Therefore, all FFE activity executions should be followed by the integral frame of strategy orientation to purposefully innovate under the established long-term strategic goals for greater NPD performance.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…Most examples for collaborations between R&D and artists occur in the development stage, when members of creative industries receive grants and are invited to join hubs, labs, panels or teams for open innovation as with Google, Meta, and Adobe. A handful of companies such as Xerox, Intel, Autodesk, Nokia Bell Labs, Vodafone, Microsoft, and Bosch pioneered and embedded artists into their R&D organisations (Sandberg, 2020). However, most of these programs had a limited scope and a short half-life.…”
Section: Reframing Randd Through Art Thinkingmentioning
confidence: 99%
“…Knowledge management is relevant to the FEI since it depends on information to support decisions and ideation (Massey et al, 2002;Song et al, 2007;Harvey et al, 2015). Technology management and R&D clarify that the FEI embraces both technology and product development ideas and decisions (Russell and Tippett, 2008;Brem and Voigt, 2009;Gonzalez, 2014;Sandberg, 2020).…”
Section: Frequency Of Publicationsmentioning
confidence: 99%
“…, 2015). Technology management and R&D clarify that the FEI embraces both technology and product development ideas and decisions (Russell and Tippett, 2008; Brem and Voigt, 2009; Gonzalez, 2014; Sandberg, 2020).…”
Section: Analysis Of the Fei Publications And Intellectual Structurementioning
confidence: 99%